Regulation of hematopoietic and leukemia stem cells by regulatory T cells - Riether, Carsten (Frontiers in Immunology, 2022)
Adult bone marrow (BM) hematopoietic stem cells (HSCs) are maintained in a quiescent state and sustain the continuous production of all types of blood cells. HSCs reside in a specialized microenvironment the so-called HSC niche, which equally promotes HSC self-renewal and differentiation to ensure the integrity of the HSC pool throughout life and to replenish hematopoietic cells after acute injury, infection or anemia. The processes of HSCs self-renewal and differentiation are tightly controlled and are in great part regulated through cellular interactions with classical (e.g. mesenchymal stromal cells) and non-classical niche cells (e.g. immune cells). In myeloid leukemia, some of these regulatory mechanisms that evolved to maintain HSCs, to protect them from exhaustion and immune destruction and to minimize the risk of malignant transformation are hijacked/disrupted by leukemia stem cells (LSCs), the malignant counterpart of HSCs, to promote disease progression as well as resistance to therapy and immune control. CD4+ regulatory T cells (Tregs) are substantially enriched in the BM compared to other secondary lymphoid organs and are crucially involved in the establishment of an immune privileged niche to maintain HSC quiescence and to protect HSC integrity. In leukemia, Tregs frequencies in the BM even increase. Studies in mice and humans identified the accumulation of Tregs as a major immune-regulatory mechanism. As cure of leukemia implies the elimination of LSC, the understanding of these immune-regulatory processes may be of particular importance for the development of future treatments of leukemia as targeting major immune escape mechanisms which revolutionized the treatment of solid tumors such as the blockade of the inhibitory checkpoint receptor programmed cell death protein 1 (PD-1) seems less efficacious in the treatment of leukemia. This review will summarize recent findings on the mechanisms by which Tregs regulate stem cells and adaptive immune cells in the BM during homeostasis and in leukemia.